Seroprevalence of measles antibody among immigrants in Gwangju, South Korea - Ran Lee; Ran Lee; Sarah Kim; Hyerin Na; Ji In Seo; Jang Gwon Yoon; Jang Gwon Yoon; A Ram Park; So Hyun Bae; So Yeong Park; Jun Hwi Cho; Jun Hwi Cho; et al. (Frontiers in Public Health)
IntroductionMeasles remains a public health concern, particularly among populations with suboptimal vaccination coverage, including immigrants. Understanding the seroprevalence of measles antibodies in immigrant populations is essential to inform tailored vaccination strategies and reduce the risk of measles reintroduction.MethodsThis study evaluated measles IgG seroprevalence among 651 immigrants from 30 countries residing in Gwangju, South Korea. Participants were recruited between September 2022 and August 2024, and measles antibody levels were assessed using the LIAISON® XL assay. Statistical analyses included Fisher’s exact and chi-squared tests to identify associations between seropositivity and demographic factors.ResultsMeasles antibody positivity rates varied significantly by age group (p < 0.01). Individuals born after 1995 exhibited the lowest seroprevalence (63.7%), while those born in 1964 or earlier were all seropositive (100%). Seroprevalence was particularly low among immigrants from Russia (68.1%), Kazakhstan (70.6%), Ukraine (72.7%), Mongolia (75.5%), and Cambodia (78.1%). Long-term residents demonstrated higher antibody positivity (92.9%) than other visa categories (p < 0.01), and women had higher seropositivity (85.8%) compared to men (80.0%), with a near-significant difference (p = 0.05).DiscussionThe higher seropositivity observed among long-term residents and women is likely due to prior immunization with the MMR (Measles Mumps Rubella) vaccine, which is recommended to prevent congenital rubella syndrome as part of pre-pregnancy vaccination protocols. This study underscores the importance of implementing tailored vaccination programs based on the characteristics of immigrant populations and focusing on countries with low seroprevalence to effectively prevent measles reintroduction.